THE INTERPERSONAL FUNCTION OF PRESIDENT JOKO WIDODO'S SPEECH AT THE COP26 SUMMIT IN GLASGOW - Rina . Mulya; Dina . Sartika (LINGUISTIK TERAPAN, 2022)
This study addresses Mood Types of interpersonal function and the realization of speech function in Mood types. Language has its own speech function to provide, to elicit, to influence, and to initiate information and also the way how it's implemented. This function can be analyzed through an interpersonal function using the principal grammar system; Mood. This study is categorized as qualitative research. It aimed to find out the Mood Types, the realization of speech function in Mood Types, and the action of the illocutionary act that was performed behind the language in President Joko Widodo’s speech at the COP26 summit in Glasgow. The findings showed that there are 3 Mood types such; 18 (75%) for declarative, 4 (17%) for imperative, and 2 (8%) for interrogative. Also, the findings showed that the realization of speech functions in Mood types are statement, command, and question. In addition, the illocutionary acts found are representative, directive, commissive, and expressive.